KERAGAMAN FUNGSI TANAMAN PAKAN DALAM SISTEM PERKEBUNAN - Rahmi Dianita (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Herbaceous forages in plantation system could be categorized into two groups that are  native and introduction species. These groups are species which have adaptability to ecophysiological condition as the growth of plantation trees. Some of these native species have multi functions/benefits. Inspite of as forage with good quality properties and used as amandement, these forage have nutraceuticals (phytochemical) function; it has active compound which roles as curing and preventing disease and also as pesticide. These active compounds may be formed as alkaloids, flavonoids, saponin and tannin. These active compound also found in introduction species such as Arachis pintoi which known have active compound from alkaloids and flavonoids that roles as antimicrobial/ natural pesticide which come from root and as antioxidant which found in leaves. The latest research found that there is an increase of these active compounds by arbuscular mycorrhizal fungi inoculation. This fungi known has benefits for enhancement root system and nutrient absorbtion for plant in integration system.